Efficacy and safety of tanezumab, NSAIDs, and placebo in patients with moderate to severe hip or knee osteoarthritis and a history of depression, anxiety, or insomnia: post-hoc analysis of phase 3 trials. (2nd November 2022) - Mease, Philip; Kuritzky, Louis; Wright, Wendy L.; Mallick-Searle, Theresa; Fountaine, Robert; Yang, Ruoyong; Sadrarhami, Mojgan; Faison, Warachal; Johnston, Elizabeth; Viktrup, Lars
Abstract: Objective: Treatment outcomes for chronic pain can be poor in patients with depression, anxiety, or insomnia. This analysis evaluated the efficacy and safety of subcutaneous tanezumab, nonsteroidal anti-inflammatory drugs (NSAIDs), and placebo in patients with osteoarthritis (OA) and a history of these conditions using data from three phase 3 studies. Methods: A post-hoc analysis of data from two pooled placebo-controlled studies and one NSAID-controlled study of subcutaneous tanezumab. All patients had moderate to severe knee or hip OA that was inadequately controlled with standard-of-care analgesics. Efficacy outcomes were least-squares mean change from baseline to Week 16 in Western Ontario McMaster Universities OA Index (WOMAC) Pain, WOMAC Physical Function, Patient's global assessment of OA, and EQ-5D-5L scores. Results were summarized for patients with and without a history of depression, anxiety, or insomnia at baseline. Results: 1545 patients were treated in the pooled placebo-controlled studies (history of depression, 12%; anxiety, 8%; insomnia, 10%; any, 23%) and 2996 in the NSAID-controlled study (16%, 11%, 13%, 28%, respectively). In groups with positive histories, 38–80% took antidepressant or anxiolytic medications at baseline. Within treatments, largely similar improvements in efficacy outcomes were observed in patients with and without a history of depression, anxiety, or insomnia; the types of treatment-emergent adverse events were similar. Conclusions: Patients with OA and a history of depression, anxiety, or insomnia did not appear to experience reduced efficacy outcomes or an altered safety profile in response to tanezumab or NSAID treatment as compared with those without. NCT02697773; NCT02709486; NCT02528188